“Healing”: Pemahaman dan Praktiknya dalam Pariwisata Berdasarkan Konten Media Sosial TikTok - Wulandini, Indah (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2025)
This study examines the understanding and practice of healing in tourism activities in Yogyakarta, which is influenced by the social media platform TikTok. The phrase